AB1085 ASSESSMENT OF DIAGNOSTIC DELAY IN PATIENTS AFFECTED BY ENTEROPATHIC SPONDYLOARTHRITIS: A CROSS-SECTIONAL STUDY. (2nd June 2020) - Conigliaro, P.; Chimenti, M. S.; D'antonio, A.; Wlderk, A.; Sichi, L.; Triggianese, P.; Sabuzi, F.; Sena, G.; Alfieri, N.; Da Ros, V.; Biancone, L.; Perricone, R.
Abstract : Background: Diagnostic delay of spondyloarthritis (SpA) has been established even in combination with inflammatory bowel disease and may contribute to radiographic progression and disability. Objectives: We aimed to evaluate diagnostic delay in enteropathic SpA (eSpA) and explore associated demographic, clinical, and radiographic characteristics. Methods: We analysed consecutive eSpA patients referred to the combined gastro-rheumatologic clinic of the University of Rome Tor Vergata. Diagnostic delay was defined as the time interval from the date of first symptoms to the date of diagnosis. Conventional radiography (CR) and magnetic resonance images (MRI) of sacroiliac (SI) joints and spine were performed in axial (ax)SpA patient and examined by two independent radiologists. MRI were assessed for the presence of active/chronic inflammatory lesions, disease activity by ASDAS and inflammatory markers. Statistical analyses were performed using Mann-Whitney, chi square/Fisher tests and covariance analysis (SPSS software). Results: 190 eSpA patients (124 female, mean age 47.5±12.8 years, disease duration 72±67.4 months, 73 UC/117 CD; 118 peripheral SpA, 72 axSpA including 44 non radiographic (nr)-axSpA) were evaluated. Axial eSpA patients had a higher prevalence of men sex (p<0.0001), HLA-B27 positivity (p=0.004), uveitis (p=0.01) and pancolitis (p<0.006) compared with peripheral eSpA. AxeSpA patients displayed higher ESR, ASDAS, and VAS pain compared with peripheral ESpA (p=0.0006, p=0.001, p=0.019, respectively). A higher prevalence of csDMARDs was detected in peripheral eSpA compared with axSpA (p=0.002) while treatment with cs and bDMARDs was similar in rad-axSpA and nr-axSpA patients. Median diagnostic delay in eSpA was 48 months (IQR 6-77) with no difference between axial and peripheral patients. Rad-ax-SpA patients displayed a higher diagnostic delay compared with nr-axSpA (median/IQR 36/17-129 vs 31/10-57 months, p=0.03). Patients with rad-axSpA were older and with longer disease duration than patients with nr-axSpA (p=0.005 and p=0.019). Low education status and high rate of employment were found in rad-axSpA compared with nr-axSpA (p=0.003 and p=0.03, respectively). Rad-axSpA patients with sclerosis, syndesmophytes and bridge at CR had a higher diagnostic delay than those without lesions (p=0.03, p=0.043, p<0.0001, Fig. 1A -C). Men showed a higher prevalence of spine damage lesions than women as sclerosis (p=0.02), squaring (p=0.0006), syndesmophytes (p=0.0028) and bridges (p=0.007). Longer disease duration was detected in patients with radiographic damage as bridge (p<0.0001) and sacroiliitis grade 3 (p=0.04). On MRI, SI bone oedema was associated with reduced diagnostic delay (p=0.04) while bone erosions was associated with higher diagnostic delay (p=0.002) compared with that in patients without these lesions (Fig. 1D-E). Rad-axSpA women had a higher prevalence of SI damage lesions at MRI than men (p=0.001). Patients with psoriasis displayed a higher diagnostic delay compared to those without skin involvement (p=0.004). Conclusion: Demographic and clinical factors differentiate axSpA from nr-axSpA patients. Diagnostic delay was higher in rad-axSpA compared with nr-axSpA despite the same treatment. Some lesions of spine/SI at CR and MRI, and psoriasis, were mostly associated with diagnostic delay and sex. Disclosure of Interests: None declared